PESATNYA PELANGGAN TERHADAP SUATU RESTAURANT AYAM BAKAR YANG MENGGUNAKAN TEKNIK PEMASARAN E-COMMERCE - Riska Febrianti Aulia Sutrasman (JEBS (Journal of Economic and Business Student), 2023)
Restaurant means a micro, small and medium enterprise which is organized commercially. Currently, there are restaurants where the process of using transactions is carried out online. Using electronic marketing means that it has become a new tradition in this modern era. Electronic commerce software is an application that is often used by the public to order something through online software such as: (shopee, tokopedia, bukalapak, etc.). Using this marketing technique can be an expansion of a business's marketing strategy. The payment method used here is to use electronic transactions. The type of E-commerce used here is the transportation sector such as gojek, etc. The principle of using this e-commerce software is to expand marketing through e-commerce. The purpose of this research is to attract as many customers as possible which have been widely disseminated about the restaurant and introduce the restaurant through the electronic commerce application. This can generate the maximum profit. The method used in this study is to use qualitative data using interview analysis. So it can be concluded that the results of this research are that grilled chicken restaurants have experienced a very rapid increase because they use marketing through e-commerce